Sino-Japanese relations at the turn of the century some implications for the Philippines - Torio, Tita (1999)
The paper examines the bilateral relations of China and Japan, Asia's regional heavyweights at the close of the 20th century. Given their past and present economic and political records, both countries are expected to play a pivotal role in the shaping of the region and the world in the next century. The relations between China and Japan have elements of cooperation and confrontation. Whether they end up as friends or foes, the relations between the two countries will have implications for the Philippines where both have historical ties and trade interests. If Sino-Japanese relations continue to be cordial, the Philippines can benefit from the synergy of their economic and political activities. But if Sino-Japanese relations become adversarial, there is the possibility of an Asian crisis that will have far-reaching economic and political repercussions especially to relatively weak countries like the Philippines.